A self-recalibration method based on scale-invariant registration for structured light measurement systems. (January 2017) - Chen, Rui; Xu, Jing; Zhang, Song; Chen, Heping; Guan, Yong; Chen, Ken
Abstract: The accuracy of structured light measurement depends on delicate offline calibration. However, in some practical applications, the system is supposed to be reconfigured so frequently to track the target that an online calibration is required. To this end, this paper proposes a rapid and autonomous self-recalibration method. For the proposed method, first, the rotation matrix and the normalized translation vector are attained from the fundamental matrix; second, the scale factor is acquired based on scale-invariant registration such that the actual translation vector is obtained. Experiments have been conducted to verify the effectiveness of our proposed method and the results indicate a high degree of accuracy. Abstract : Highlights: The normalized translation vector is obtained from the fundamental matrix. The actual translation vector is acquired from scale-invariant registration. Experiments have been conducted to verify the effectiveness of proposed method.